1992
DOI: 10.3109/00365529209000088
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal Ulcer and Eradication ofHelicobacter pyloriin a Developing Country An 18-Month Follow-up Study

Abstract: Forty-eight patients with endoscopically proven duodenal ulcer (DU) and Helicobacter pylori infection detected by 14C-urea breath test (BT) were assigned to 5 days of treatment with furazolidone, metronidazole, and amoxicillin in addition to eventual classical anti-ulcer agents if necessary. Clinical evaluation and BT were repeated at 2, 6, and 18 months after therapy to determine H. pylori eradication or reinfection. Endoscopy was also repeated at 6 and 18 months after treatment to detect DU relapse. In 29 (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
2

Year Published

1994
1994
2003
2003

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(31 citation statements)
references
References 20 publications
2
27
0
2
Order By: Relevance
“…Reported reinfection rates range from 0 (22) to 100% (18). Coelho et al, from Brazil, reported that six of 29 eradicated patients (20%) became reinfected after 18 months of follow-up (20). From a subsequent report of 147 patients, reported only in abstract form, Parsonnet estimated a reinfection rate of 8.8%/yr (1).…”
Section: Discussionmentioning
confidence: 99%
“…Reported reinfection rates range from 0 (22) to 100% (18). Coelho et al, from Brazil, reported that six of 29 eradicated patients (20%) became reinfected after 18 months of follow-up (20). From a subsequent report of 147 patients, reported only in abstract form, Parsonnet estimated a reinfection rate of 8.8%/yr (1).…”
Section: Discussionmentioning
confidence: 99%
“…Reinfection in adults in developed countries is quite rare but has been found in 20% of patients in Brazil within 18 months of eradication. 9 This finding has clear clinical implications for the value of treating H. pylori infection in developed vs.…”
Section: Epidemiologymentioning
confidence: 99%
“…Estudos clínicos e moleculares, porém, indicam que a recrudescência da infecção e a transmissão iatrogênica são responsáveis por grande parte dos casos de soroconversão pós-tratamento, particularmente quando ocorre nos primeiros 12 meses após a erradicação do agente. 19,24,45,125,134,145 Nos países em desenvolvimento, a reinfecção pós-sucesso terapêutico é freqüente (aproximadamente 50% dos casos), atingindo índices de até 100% dos casos ao ano, como se pode observar no Peru. 120 Entretanto, nos países industrializados, a taxa de reinfecção varia entre 0,6% a 4,7% ao ano.…”
Section: Taxa De Reinfecçãounclassified